2013
DOI: 10.1016/j.prevetmed.2013.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A(H1N1)pdm09 virus infection in Norwegian swine herds 2009/10: The risk of human to swine transmission

Abstract: Influenza A viruses cause respiratory infection in humans and pigs, and some serotypes can be transmitted between these species. The emergence of influenza A(H1N1)pdm09 virus infections in the spring of 2009 quickly led to a worldwide pandemic in humans, with subsequent introduction of the virus to pig populations. Following a widespread infection in the human population in Norway, influenza A(H1N1)pdm09 virus was introduced to the influenza A naïve Norwegian pig population, and within a few months pigs in mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 19 publications
1
25
1
2
Order By: Relevance
“…Previous studies have shown that people working with pig herds may have transmitted H1N1pdm09 to pigs [7, 12, 16, 18, 20, 28]. Here in Norway, reverse zoonosis of humans carrying the virus and infecting the pigs they are in contact with remained highly probable during the study period.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies have shown that people working with pig herds may have transmitted H1N1pdm09 to pigs [7, 12, 16, 18, 20, 28]. Here in Norway, reverse zoonosis of humans carrying the virus and infecting the pigs they are in contact with remained highly probable during the study period.…”
Section: Discussionmentioning
confidence: 89%
“…Biochemical data predicted in H1N1, H3N2, H7N9, and H5N1 strains. Based on the preliminary motif described above, we screened the whole protein sequences of four current epidemic IAV strains: A/Beijing/01/2009 (H1N1), A/Texas/50/2012 (H3N2), A/chicken/Nigeria/SO494/2006 (H5N1), and A/Shanghai/ 4664T/2013 (H7N9) (54)(55)(56)(57). There were 28 total 9-mer epitope peptides that were predicted to fit the motif.…”
Section: Distinct Overall Structures Of Two Psla-3*hs0202 Complexesmentioning
confidence: 99%
“…Pigs are a particularly important species in this regard as the occurrence of both types of SA receptors permits binding of human and avian influenza viruses making them an efficient ‘mixing vessel' 11, 12, 13, 14. Interspecies transmission (in both directions) of swine and human influenza viruses is well recognised, evidenced by the isolation of human influenza virus in swine15, 16 and evidence of swine influenza virus (SIV) infection in people with close occupational17, 18, 19 and/or residential proximity to pigs20, 21; or prolonged exposure at an agricultural fair22. Transmission between pigs and bird species is exemplified by various reports of isolation of SIV from turkeys 23, 24, 25.…”
Section: Introductionmentioning
confidence: 99%